Ewing sarcoma of the left big toe with trans-articular skip lesion (Faculty of Medicine Universitas Indonesia, 2009)
We report the case of the patient who had Ewing Sarcoma in whom radiological and hystopathological appearances revealed a tumor mass in the left big toe along with trans-artikular skip lesion on the left diaphysis of tibia. In Cipto Mangunkusomo Hospital since 1995 until 2004 we have found 20 Ewing sarcoma cases, but only one skip lesion Ewing sarcoma was found. The diagnosis of transarticular skip lesion in association of Ewing sarcoma was confirmed in clinicopathological conferrence. The initial evaluation of all patients included the recording of the medical history, physical examination, and hematological studies. Radiographs of the chest and the site of the primary tumor were made routinely. Systemic staging was performed with use of total-body bone scan. Ray amputation of left big toe and open biopsy from mass of mid-shaft of tibia had been done to confirm the diagnosis. The patient underwent induction chemotherapy and above knee amputation. Ten months after diagnosis, he died because of advanced-distant metastasis. (Med J Indones 2008; 18: 139-44)Key words: Ewing sarcoma, trans-articular skip lesion